Inovasi Pelayanan Publik pada Pemerintah Daerah di Indonesia - Farhan, Akhmad (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2023)
Innovation has been popular in industry and services owned by the private sector. Currently, many innovations have also been carried out by the public sector. However, there are still few studies that discuss public sector innovations that have been carried out by provincial, district and city governments. Therefore, this article attempts to answer the question what is the typology innovation? what is the category of innovation carried out by local governments in Indonesia? how is the distribution of local governments that have made innovations? This study uses qualitative methods by conducting secondary data analysis. The data analysis technique used has four stages, namely data collection, data reduction, data presentation and the last step is drawing conclusions. The results of innovation data analysis conducted by the public sector including local governments from 2014 to 2022 show that the number of innovations carried out continues to grow rapidly. The typology of innovation analyzed in this study shows that the four major types of innovation carried out by local governments are process technology, social innovation, new services and administration. The categories of innovation that are mostly carried out are in the fields of health, administration, governance, education, community empowerment, economic growth and employment opportunities. The distribution of innovations implemented by the provincial government is visible in the form of a map dominated by the provinces on the island of Java except for Banten. To implement the innovation in all regions, it starts with a common understanding of the importance of innovation. Moreover, the political will of regional leaders to improve public services is very important.